Sex-Based Difference in Aortic Dissection Outcomes: A Multicenter Study - Francesco Nappi; Sandra Petiot; Antonio Salsano; Sanjeet Singh Avtaar Singh; Joelle Berger; Marisa Kostantinou; Severine Bonnet; Ivancarmine Gambardella; Fausto Biancari; Almothana Almazil; Francesco Santini; Rim Chaara; et al. (Journal of Cardiovascular Development and Disease, 2023)
Background: Type A Acute Aortic Dissection (TAAAD) repair is a surgical emergency associated with high morbidity and mortality. Registry data have noted several sex-specific differences in presentation with TAAAD which may account for the differences in men and women undergoing surgery for this condition. Methods: A retrospective review of data from three departments of cardiac surgery (Centre Cardiologique du Nord, Henri-Mondor University Hospital, San Martino University Hospital, Genoa) between January 2005 and 31 December 2021 was conducted. Confounders were adjusted using doubly robust regression models, a combination of regression models with inverse probability treatment weighting by propensity score. Results: 633 patients were included in the study, of which 192 (30.3%) were women. Women were significantly older with reduced haemoglobin levels and pre-operative estimated glomerular filtration rate compared to men. Male patients were more likely to undergo aortic root replacement and partial or total arch repair. Operative mortality (OR 0.745, 95% CI: 0.491–1.130) and early postoperative neurological complication results were comparable between the groups. The adjusted survival curves using IPTW by propensity score confirmed the absence of a significant impact of gender on long-term survival (HR 0.883, 95% CI 0.561–1.198). In a subgroup analysis of women, preoperative levels of arterial lactate (OR 1.468, 95% CI: 1.133–1.901) and mesenteric ischemia after surgery (OR 32.742, 95% CI: 3.361–319.017) were significantly associated with increased operative mortality. Conclusions: The advancing age of female patients alongside raised preoperative level of arterial lactate may account for the increasing preponderance among surgeons to perform more conservative surgery compared to their younger male counterparts although postoperative survival was similar between the groups.